Incidencia de la evasión del impuesto a la renta en la Situación Económica y Financiera de las Mypes del sector Abarrotes en el distrito de Tarapoto. Periodo 2013 - Pinedo Honorio, Laxmi Rossmeri (2015)
Tax Evasion is a problem that exists in most countries, especially in less developed because there is no tax awareness and structure of the tax system is not adequate, affecting tax revenues, causing a harmful effect to society; yet is poorly investigated. This paper entitled “IMPACT OF EVASION OF INCOME TAX ON THE ECONOMIC AND FINANCIAL SITUATION OF THE GROCERY SECTOR MYPES DISTRICT OF TARAPOTO. YEAR 2013 " aims to determine the causes that are associated with tax evasion in companies formally constituted and informality traders stores located in the district of Tarapoto , so it is expected the work constitutes a valuable contribution to the development of Sector Trade . In this regard, the research was conducted using as a research method survey, with the sample of 59 commercial companies grocery located in the District of Tarapoto. The results show us that the causes that are associated with tax evasion in the Merchants are the desire to generate more income (profits), the excess burden and complexity to tax and ultimately benefiting from regimes that is not theirs. So we conclude that the State should have an attitude of transparency so that taxpayers can be confident that their money is used to benefit themselves and others and is an engine that encourages the duty to pay taxes that every citizen should have.